An investigation of building information modelling functions in the Palestinian construction industry - Enshassi, A.; AbuHamra, L. (Revista Ingeniería de Construcción, 2016)
The objective of this paper is to investigate the importance of Building Information Modelling (BIM) functions in the construction industry from professionals’ views in the Gaza Strip-Palestine. A questionnaire survey was employed in this study and 270 professionals in the construction industry have responded to the questionnaire; data were analyzed using exploratory factor analysis. The study findings indicated that BIM functions are significantly needed and important for professionals in the construction industry in Gaza Strip. Findings of this study revealed three components of BIM functions: data management and utilization in planning, operation and maintenance, visualized design and analysis, and construction and operation. Energy optimization was found as the highest important function of BIM of the first component as there is a high demand for sustainable building and sustainable development. A functional simulation in order to choose the best solution for lighting and energy was the highest important function of the second component. This function will assist in identifying methods to reduce resources consumption and increase on-site renewable opportunities. Model-based cost estimation was found the highest important function in the third component. Professionals in the construction industry will benefit from the findings presented in this paper by understanding the BIM functions which will encourage them to apply BIM tools that will lead to a substantial improvement in the performance of construction projects.